A longitudinal investigation into the relative age effect in an English professional football club: exploring the 'underdog hypothesis'. Issue 2 (2nd April 2020) - Kelly, Adam L.; Wilson, Mark R.; Gough, Lewis A.; Knapman, Harry; Morgan, Paul; Cole, Matthew; Jackson, Daniel T.; Williams, Craig A.
ABSTRACT: Purpose: The relative age effect (RAE) refers to the bias influence of birthdate distribution, with athletes born later in the selection year being under-represented in talent development systems. However, the 'underdog hypothesis' suggests that younger birth quarter (BQ) athletes are over-represented among those who successfully transition from youth systems to senior professional status. Methods: Accordingly, the purpose of this study was twofold; (1) to provide further test of the RAE over twelve seasons ( n = 556), and (2) to examine the BQ of professional contracts awarded to academy graduates at an English professional football club over eleven seasons ( n = 364). Results: Significantly skewed ( P < 0.001) birthdate distributions were found for academy players (BQ1 n = 224: BQ2 n = 168; BQ3 n = 88; BQ4 n = 76). The distribution from academy graduates was also significantly skewed for professional contracts awarded ( P = 0.03), with greater BQ4 representation ( n = 8) compared to other BQs (BQ1 n = 5; BQ2 n = 8; BQ3 n = 6). Conclusion: These findings are indicative that the RAE continues to manifest within an academy setting. Interestingly however, the underdog hypothesis shows BQ4s were approximately four times more likely to achieve senior professional status compared to BQ1s. Implications for talent identification and development in football are discussed.